Community Group Strategies for Increasing Participation in the Probebaya Program: Strategi Kelompok Masyarakat untuk Meningkatkan Partisipasi dalam Program Probebaya - Taufik Rahman; Abdul Rofik; Ahmad Yani; Trisna Waty Riza Eryani (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Optimal community participation is a key determinant of success in community-based development programs, such as the Probebaya Program in Samarinda City, which integrates infrastructure development and economic empowerment at the village level. Specific Background: In Sempaja Barat Subdistrict, community participation remains low, influenced by dependence on incentives, limited awareness, and minimal involvement of Community Groups (POKMAS) in all program stages. Knowledge Gap: Previous studies rarely examine in detail the specific roles of POKMAS, along with supporting and inhibiting factors, in the context of Probebaya at the village level. Aims: This study analyzes the role of POKMAS in enhancing community participation and identifies the factors influencing its effectiveness. Results: Using a descriptive qualitative method, the research found that POKMAS plays a strategic role in coordinating community deliberations, implementing activities, and evaluating programs, with support from community leaders and the government as enabling factors, and limited budget, miscommunication, and low awareness as major constraints. Novelty: This study provides a detailed mapping of POKMAS’ roles and the factors influencing community participation in Probebaya at the local level. Implications: The findings highlight the need to strengthen POKMAS capacity, raise public awareness, and foster synergy among stakeholders to ensure program sustainability and effectiveness. Highlights: Strategic Role of POKMAS, Coordinating community meetings, program implementation, and evaluation for the Probebaya Program. Inhibiting Factors, Low public awareness, dependence on incentives, and miscommunication. Key Recommendations, Strengthening POKMAS capacity, raising community awareness, and fostering stakeholder synergy. Keywords: Community Participation, POKMAS, Probebaya Program, Local Development, Public Empowerment